(untitled) (Texas Journal of Philology, Culture and History, 2024)
This article discusses the integration of corpora analysis into English language teaching. It highlights the benefits, methodologies, and potential challenges associated with incorporating corpora analysis in the classroom. The author explains that corpora, which are large collections of written and spoken texts, provide teachers and learners with authentic language data to facilitate language learning and teaching. The article presents various methods for implementing corpora analysis, including selecting suitable corpora, introducing learners to corpora tools and software, and incorporating corpus-based activities into the curriculum